1999
DOI: 10.1007/s002709900368
|View full text |Cite
|
Sign up to set email alerts
|

Venous sac embolization of pulmonary arteriovenous malformation: Preliminary experience using interlocking detachable coils

Abstract: Venous sac embolization may be beneficial in PAVMs with large out-flow vessels or short feeding arteries. IDCs are suitable for this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…We placed anchoring detachable coils and did not encounter this major complication. In general, the diameter of the venous sac is larger than of the draining vein which, in turn, is larger than the feeder (5,14). In our series the mean diameter of the venous sac, drainers, and feeders was 8.4, 4.1, and 3.7 mm, respectively.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…We placed anchoring detachable coils and did not encounter this major complication. In general, the diameter of the venous sac is larger than of the draining vein which, in turn, is larger than the feeder (5,14). In our series the mean diameter of the venous sac, drainers, and feeders was 8.4, 4.1, and 3.7 mm, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Although venous sac embolization of PAVMs has been reported to risk intraprocedural rupture and coil protrusion into normal pulmonary veins (5,10,11), we found that it was safe and reduced the incidence of post-treatment reperfusion. We now present a retrospective evaluation of its safety and outcomes in a mid-term follow-up study of venous sac embolization to treat patients with PAVMs.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…For venous sac embolization of pulmonary arteriovenous malformations, Takahashi et al (8) used interlocking detachable coils with a diameter 10% larger than the structure to be embolized. Hashimoto (5) recommended that the coil diameter should be 20–50% larger than that of the target vein and up to two times larger for venous embolization.…”
Section: Discussionmentioning
confidence: 99%
“…In case of a short feeding artery, venous sac occlusion is necessary with the use of detachable microcoils. 18 If the size of the venous sac is not diminished on the follow-up chest X-ray film and computed tomography (CT) at 6 months to 1 year, the feeding artery may be recanalized; or there may have been a missed feeding artery, and reembolization is necessary.…”
Section: Pulmonary Avmsmentioning
confidence: 99%